2014
DOI: 10.1021/ci5004653
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Inhibitors of Schistosoma mansoni HDAC8 by Combining Homology Modeling, Virtual Screening, and in Vitro Validation

Abstract: Schistosomiasis, caused by S. mansoni, is a tropical disease that affects over 200 million people worldwide. A novel approach for targeting eukaryotic parasites is to tackle their dynamic epigenetic machinery that is necessary for the extensive phenotypic changes during their life cycle. We recently identified S. mansoni histone deacetylase 8 (smHDAC8) as a potential target for antiparasitic therapy. Here we present results from a virtual screening campaign on smHDAC8. Besides hydroxamates, several sulfonamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 53 publications
0
90
0
Order By: Relevance
“…This conformation creates a larger active site which should accommodate larger inhibitors compared to human HDAC8 and, therefore, offers the possibility for organism-specific inhibition. Indeed, smHDAC8 has been inhibited by the traditional HDACi SAHA and M344, as well as bulky ‘linkerless’ hydroxamate inhibitors (Kannan, et al, 2014; Heimburg, et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…This conformation creates a larger active site which should accommodate larger inhibitors compared to human HDAC8 and, therefore, offers the possibility for organism-specific inhibition. Indeed, smHDAC8 has been inhibited by the traditional HDACi SAHA and M344, as well as bulky ‘linkerless’ hydroxamate inhibitors (Kannan, et al, 2014; Heimburg, et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that, in many cases, IC 50 values are very similar but may differ with different substrates by up to 20-fold in potency for certain inhibitors [42].…”
Section: Reviewmentioning
confidence: 99%
“…So far, only a few series of Sm HDAC8 inhibitors have been reported, and most were only moderately effective against the parasite or showed no effect (Figure ). Based on virtual screening and structure‐guided optimization of a co‐crystallized hit ( J1038 , Figure ), we recently described a benzamidohydroxamic acid TH65 (Figure ) as an Sm HDAC8 inhibitor that is able to kill S. mansoni larvae in culture …”
Section: Introductionmentioning
confidence: 99%